Merkel cell polyomavirus protein ALTO modulates TBK1 activity to support persistent infection. - Ranran Wang; Taylor E Senay; Tiana T Luo; Wei Liu; James M Regan; Nicholas J H Salisbury; Denise A Galloway; Jianxin You (PLoS Pathogens, 2024)
While Merkel cell polyomavirus (MCPyV or MCV) is an abundant virus frequently shed from healthy skin, it is one of the most lethal tumor viruses in immunocompromised individuals, highlighting the crucial role of host immunity in controlling MCPyV oncogenic potential. Despite its prevalence, very little is known about how MCPyV interfaces with the host immune response to maintain asymptomatic persistent infection and how inadequate control of MCPyV infection triggers MCC tumorigenesis. In this study, we discovered that the MCPyV protein, known as the Alternative Large Tumor Open Reading Frame (ALTO), also referred to as middle T, effectively primes and activates the STING signaling pathway. It recruits Src kinase into the complex of STING downstream kinase TBK1 to trigger its autophosphorylation, which ultimately activates the subsequent antiviral immune response. Combining single-cell analysis with both loss- and gain-of-function studies of MCPyV infection, we demonstrated that the activity of ALTO leads to a decrease in MCPyV replication. Thus, we have identified ALTO as a crucial viral factor that modulates the STING-TBK1 pathway, creating a negative feedback loop that limits viral infection and maintains a delicate balance with the host immune system. Our study reveals a novel mechanism by which a tumorigenic virus-encoded protein can link Src function in cell proliferation to the activation of innate immune signaling, thereby controlling viral spread, and sustaining persistent infection. Our previous findings suggest that STING also functions as a tumor suppressor in MCPyV-driven oncogenesis. This research provides a foundation for investigating how disruptions in the finely tuned virus-host balance, maintained by STING, could alter the fate of MCPyV infection, potentially encouraging malignancy.